Probing structural holes in disordered ionic systems - Pastore, G; Tatlipinar, H; Tosi, MP (EDITRICE COMPOSITORI BOLOGNA, 1998)
Statistical-mechanical equations for pair correlations in a partly quenched ionic system are used to evaluate the structure taken by an annealed fluid of cations permeating a quenched disordered matrix of anions. Two types of structural information are obtained: 1) the structural holes in the matrix which are preferentially occupied by the annealed fluid are selected through the choice of the cation-anion potential; and 2) the correlations between pairs of such structural holes emerge by varying the concentration of the annealed fluid. Illustrations are presented for disordered states of models of NaCl and CuCl. The possible usefulness of this method of structural analysis for models of ionic glasses is briefly discussed.
Keywords: EQUATIONS; MEDIA; Physics